Establishing determinants and quality indicators for getting home alive following moderate to severe traumatic brain injury: the Australian Traumatic Brain Injury National Data Project. (15th September 2021) - O'Reilly, Gerard M; Curtis, Kate; Kim, Yesul; Rushworth, Nick; Mitra, Biswadev; Tee, Jin; Hunter, Kate; Ryder, Courtney; Hendrie, Delia; Fitzgerald, Mark C
Abstract: Moderate to severe traumatic brain injury (TBI) contributes to a significant burden across Australia. However, the data required to inform targeted equitable system‐level improvements in emergency TBI care do not exist. The incidence and determinants of outcomes following moderate to severe TBI in Australia remain unknown. The variation in the impact of moderate to severe TBI, according to patient demographics and injury mechanism, is poorly defined. The Australian Traumatic Brain Injury National Data Project will lead to a clear understanding, across Australia and pre‐specified subgroups (including Aboriginal and Torres Strait Islander peoples), of the incidence, determinants and impact of priority outcomes following moderate to severe TBI, including survival to discharge home. Furthermore, this project will establish a set of national clinical quality indicators for patients experiencing a moderate to severe TBI. The Australian Traumatic Brain Injury National Data Project will inform where to target emergency care system‐wide improvements. Without baseline data, efforts are wasted.